Barriers, Access, Resources and Knowledge: An Analysis of HIV Testing vis Women's Voices in Ottawa - Vannice, Sarah (Université d'Ottawa / University of Ottawa, 2016)
Women within African, Caribbean, and Black (ACB) communities are experiencing a higher burden of the HIV epidemic than other groups of women in Canada and a low uptake of HIV testing and counseling. As HIV testing is a well recognized HIV prevention strategy, increasing HIV testing within those most affected by HIV in Canada is a high priority. Therefore, this study gathers and describes the perceptions, experiences, and knowledge of HIV and HIV testing and counseling among women within ACB communities in Ottawa. These perceptions and experiences provide rich context to current barriers to HIV testing and counseling access among these groups of women; context that is utilized to ground recommendations to improve experiences of HIV testing and counseling and to increase the uptake of HIV testing and counseling among ACB women. In essence, this study provides recommendations by ACB women for ACB Women.
Keywords: HIV